Phosphorylation of serine 248 of C/EBPα is dispensable for myelopoiesis but its disruption leads to a low penetrant myeloid disorder with long latency. - Marie S Hasemann (Public Library of Science (PLoS), 2012)
Background Transcription factors play a key role in lineage commitment and differentiation of stem cells into distinct mature cells. In hematopoiesis, they regulate lineage-specific gene expression in a stage-specific manner through various physical and functional interactions with regulatory proteins that are simultanously recruited and activated to ensure timely gene expression. The transcription factor CCAAT/enhancer binding protein α (C/EBPα) is such a factor and is essential for the development of granulocytic/monocytic cells. The activity of C/EBPα is regulated on several levels including gene expression, alternative translation, protein interactions and posttranslational modifications, such as phosphorylation. In particular, the phosphorylation of serine 248 of the transactivation domain has been shown to be of crucial importance for granulocytic differentiation of 32Dcl3 cells in vitro. Methodology/principal findings Here, we use mouse genetics to investigate the significance of C/EBPα serine 248 in vivo through the construction and analysis of Cebpa(S248A/S248A) knock-in mice. Surprisingly, 8-week old Cebpa(S248A/S248A) mice display normal steady-state hematopoiesis including unaltered development of mature myeloid cells. However, over time some of the animals develop a hematopoietic disorder with accumulation of multipotent, megakaryocytic and erythroid progenitor cells and a mild impairment of differentiation along the granulocytic-monocytic lineage. Furthermore, BM cells from Cebpa(S248A/S248A) animals display a competitive advantage compared to wild type cells in a transplantation assay. Conclusions/significance Taken together, our data shows that the substitution of C/EBPα serine 248 to alanine favors the selection of the megakaryocytic/erythroid lineage over the monocytic/granulocytic compartment in old mice and suggests that S248 phosphorylation may be required to maintain proper hematopoietic homeostasis in response to changes in the wiring of cellular signalling networks. More broadly, the marked differences between the phenotype of the S248A variant in vivo and in vitro highlight the need to exert caution when extending in vitro phenotypes to the more appropriate in vivo context.